Synthesis of Cr3+-doped Al2O3 in nanoscale for bio-labels in myocardial cells - Sida Chen; Jian Hou; Yang Huang; Jinyu Pan; Kaizheng Liu; Guangxian Chen; Zhongkai Wu; Haoyi Wu (Heliyon)
The Al2O3: Cr3+ light-converting materials were successfully synthesized via co-precipitation, resulting in a grain size ranging from 100 to 400 nm. Under excitation wavelengths spanning from 360 to 650 nm, a distinct near-infrared (NIR) emission at 695 nm was observed. Through optimization, it has been established that a Cr3+ doping concentration of 1.0 mol% results from the optimal emission intensity. The material shows relatively stable in water and it was employed to cultivate the H9C2 cells, and the NIR emission from the cells was observed, indicating the successful absorption of the material by the cells. Additionally, the toxicity of the material was examined, by reducing the concentration to 2 nM/mL, the toxicity of the material was significantly reduced to a promising level. Therefore, the suitable grain size, NIR emission and the biocompatibility renders this material a candidate in cell imaging.